MAKSIMALISASI KEUNTUNGAN DENGAN KENDALA FAKTOR-FAKTOR PRODUKSI PADA KEDAI KOPI BNO - Saskia Noverina Andika Putri; Fitria Dina Riana; Anisa Aprilia (Universitas Sebelas Maret, 2024)
Kedai Kopi BNO is one of the coffee shop in Balikpapan City. However, in the last 3 months (February-April 2021) their income has decreased. It caused by the use of production factors that are less than optimal. The purpose of this study are to analyzed the maximum profit that can be obtained from the results of linear programming analysis, and also to analyzed the sensitivity to changes in variables from the results of linear programming analysis. This research was conducted in May 2021. Data processing is using Microsoft Excel Data Solver software. The result of linear programming analysis is that the maximum profit that can be obtained by Kedai Kopi BNO is Rp11,498,448.98 per month. Utilization of roasting coffee, mineral water, liquid sugar, and labor hours is optimal. Business actors can only change the value of profits and the amount of raw materials between the minimum and maximum limits so that the production activities could continue to run at the recommended optimum level.